2010
DOI: 10.1542/peds.2009-2448
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Hearing Loss Is Associated With Worse Speech-Language Scores in Children

Abstract: Objective To determine whether elementary school-aged children with unilateral hearing loss (UHL) demonstrate significantly worse language skills than their sibling controls with normal hearing, and whether they are more likely to receive extra assistance or resources at school. Patients and Methods Case-control study of age 6-12 year old children with UHL compared with sibling controls (74 matched pairs, total n=148), all with normal cognition by parental report. Scores on the oral portion of the Oral and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
230
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 309 publications
(251 citation statements)
references
References 39 publications
6
230
2
13
Order By: Relevance
“…The authors concluded that children with UHL present higher risk for socioemotional difficulties than children with normal hearing. Another study (11) that evaluated the linguistic abilities of children with UHL observed that they presented significantly lower results in the oral communication assessment than normal-hearing children subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that children with UHL present higher risk for socioemotional difficulties than children with normal hearing. Another study (11) that evaluated the linguistic abilities of children with UHL observed that they presented significantly lower results in the oral communication assessment than normal-hearing children subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In daily living, they often complain of poor stereotactic sense due to the problem of head shadowing. Not only is the hearing aspect affected, but also children with unilateral hearing loss may have poorer oral expression and oral composition [10].…”
Section: Managementmentioning
confidence: 99%
“…Aynı ailede tek taraflı işitme kaybı olan ve normal işiten çocukları karşılaştıran bir çalışmada işitme kaybı olan çocukların dil gelişiminde anlamlı gerilik saptanmıştır, ayrıca annenin eğitim düzeyi, ailenin sosyoekonomik durumu ve gelir düzeyi, çocukta ek sorunların olması, ileri/çok ileri işitme kaybı ve sağ taraflı işitme kaybı olması da bu gerilikle ilişkili anlamlı faktörler arasında yer almıştır. [11] …”
Section: Tek Tarafli İşi̇tme Kaybinin Etki̇leri̇unclassified